A possible γ-ray quasi-periodic oscillation of ∼314 days in the blazar OJ 287. Issue 1 (26th September 2020) - Kushwaha, Pankaj; Sarkar, Arkadipta; Gupta, Alok C; Tripathi, Ashutosh; Wiita, Paul J
ABSTRACT: We report the detection of a probable γ-ray quasi-periodic oscillation (QPO) of around 314 d in the monthly binned 0.1–300 GeV γ-ray Fermi -Large Area Telescope light curve of the well-known BL Lacertae blazar OJ 287. To identify and quantify the QPO nature of the γ-ray light curve of OJ 287, we used the Lomb–Scargle periodogram (LSP), REDFIT, and weighted wavelet Z-transform (WWZ) analyses. We briefly discuss possible emission models for radio-loud active galactic nuclei that can explain a γ-ray QPO of such a period in a blazar.